Organic Polymers - Sand, Arpit; Zaki, Elsayed (IntechOpen, 2020)
This book, Organic Polymers, covers aspects that are of immediate concern to a new entrant to the field of polymers. Taken as a whole, these eight chapters aim to help the readers easily assimilate other specialized and exhaustive treatises on the subject. Topics dealing with the chemistry and technology of polymers are presented in a careful and logical manner so as to provide an easy and enjoyable read. Several examples and analogies are included so to make the main concepts easy to follow and tables and figures are included so that the book can serve, to a limited extent, as a hand book dealing with polysaccharides with different parameters. This book is meant for students studying polysaccharides and those working on graft copolymers and other allied polymer industries but without a formal educational background in organic polymers.